Low-density star cluster formation: discovery of a young faint fuzzy on the outskirts of the low-mass spiral galaxy NGC 247. Issue 2 (19th October 2022) - Romanowsky, Aaron J; Larsen, Søren S; Villaume, Alexa; Carlin, Jeffrey L; Janz, Joachim; Sand, David J; Strader, Jay; Brodie, Jean P; Chakrabarti, Sukanya; Cheng, Chloe M; Crnojević, Denija; Forbes, Duncan A; et al.
ABSTRACT: The classical globular clusters found in all galaxy types have half-light radii of r h ∼ 2–4 pc, which have been tied to formation in the dense cores of giant molecular clouds. Some old star clusters have larger sizes, and it is unclear if these represent a fundamentally different mode of low-density star cluster formation. We report the discovery of a rare, young 'faint fuzzy' star cluster, NGC 247-SC1, on the outskirts of the low-mass spiral galaxy NGC 247 in the nearby Sculptor group, and measure its radial velocity using Keck spectroscopy. We use Hubble Space Telescope imaging to measure the cluster half-light radius of r h ≃ 12 pc and a luminosity of LV ≃ 4 × 10 5 L ⊙ . We produce a colour–magnitude diagram of cluster stars and compare to theoretical isochrones, finding an age of ≃300 Myr, a metallicity of [ Z /H] ∼ −0.6 and an inferred mass of M ⋆ ≃ 9 × 10 4 M⊙ . The narrow width of blue-loop star magnitudes implies an age spread of ≲50 Myr, while no old red-giant branch stars are found, so SC1 is consistent with hosting a single stellar population, modulo several unexplained bright 'red straggler' stars. SC1 appears to be surrounded by tidal debris, at the end of an ∼2 kpc long stellar filament that also hosts two low-mass, low-density clusters of a similar age. We explore a link between the formation of these unusual clusters and an external perturbation of their host galaxy, illuminating a possible channel by which some clusters are born with large sizes.